PENERAPAN MODEL PEMBELAJARAN PROJECT BASE LEARNING UNTUK MENINGKATKAN PRESTASI BELAJAR MATA KULIAH RIAS FANTASI DI AKS-AKK YOGYAKARTA - Enny Harwiyati; Helmia Cipta Rohmawati (Jurnal Socia Akademika, 2022)
The purpose of the writing is to find out the application of the Project Base Learning learning model in improving the learning achievement of the Rias Fantasi course in students of the AKS "AKK" Yogyakarta Cosmetology study program. The design of this study uses Qualitative research methods and descriptive data analysis with sampling techniques. While the object studied was the learning achievements of the Fantasy Makeup course, the research subjects were as many as 25 students of the Cosmetology study program in the fourth semester of AKS "AKK," and the data collection method in this study was observed for the results of Rias Fantasi, documentation, interviews. The results showed that the results of the Rias Fantasi Assessment on students with an A grade were six students (76%), and students with a B grade were six students (24%). Students' learning achievements are the first place in fantasy makeup in the Professional Word N-Beauty Contest competition in Korea, and the third winner in the UNJ Face Painting Make-Up Competition in 2022. To advance students, vocational education institutions strive for innovative and collaborative project-based teaching materials to form students more creative, cooperative, competitive, resilient, and ready to face the current era of digital communication so that students will gain hard skills and soft skills